Determination of β-Cyano-L-alanine, γ-Glutamyl-β-cyano-L-alanine, and Common Free Amino Acids in Vicia sativa (Fabaceae) Seeds by Reversed-Phase High-Performance Liquid Chromatography - Cristina Megías; Isabel Cortés-Giraldo; Julio Girón-Calle; Javier Vioque; Manuel Alaiz (Journal of Analytical Methods in Chemistry)
A method for determination of β-cyano-L-alanine, γ-glutamyl-β-cyano-L-alanine and other free amino acids in Vicia sativa is presented. Seed extracts were derivatized by reaction with diethyl ethoxymethylenemalonate and analyzed by reverse-phase high-performance liquid chromatography. Calibration curves showed very good linearity of the response. The limit of detection and quantification was 0.15 and 0.50 μM, respectively. The method has high intra- (RSD = 0.28–0.31%) and interrepeatability (RSD = 2.76–3.08%) and remarkable accuracy with a 99% recovery in spiked samples. The method is very easy to carry out and allows for ready analysis of large number of samples using very basic HPLC equipment because the derivatized samples are very stable and have very good chromatographic properties. The method has been applied to the determination of γ-glutamyl-β-cyano-L-alanine, β-cyano-L-alanine, and common free amino acids in eight wild populations of V. sativa from southwestern Spain.